Deletion of IRS-1 leads to growth failure and insulin resistance with downregulation of liver and muscle insulin signaling in rats - Yuka Toyoshima; Katsuyuki Nakamura; Yusuke Taguchi; Reiko Tokita; Shiho Takeuchi; Hayato Osawa; Naomi Teramoto; Hidetoshi Sugihara; Fumiaki Yoshizawa; Keitaro Yamanouchi; Shiro Minami (Scientific Reports)
Abstract Insulin receptor substrate (IRS)-1 and IRS-2 are major molecules that transduce signals from insulin and insulin-like growth factor-I receptors. The physiological functions of these proteins have been intensively investigated in mice, while little is known in other animals. Our previous study showed that the disruption of IRS-2 impairs body growth but not glucose tolerance or insulin sensitivity in rats, which led us to hypothesize that IRS-1 plays more pivotal roles in insulin functions than IRS-2. Here, we created IRS-1 knockout (KO) rats to elucidate the physiological roles of IRS-1 in rats. The body weight of IRS-1 KO rats at birth was lower than that of wild-type (WT) littermates, and postnatal growth of IRS-1 KO rats was severely impaired. Compared with WT rats, IRS-1 KO rats displayed insulin resistance but maintained euglycemia because of compensatory hyperinsulinemia. In addition, despite the increased activity of insulin-stimulated IRS-2-associated phosphatidylinositol-3 kinase (PI3K), insulin-induced phosphorylation of the kinases downstream of PI3K was suppressed in the liver and skeletal muscle of IRS-1 KO rats. Taken together, these results indicate that in rats, IRS-1 is essential for normal growth and the glucose-lowering effects of insulin. IRS-1 appears to be more important than IRS-2 for insulin functions in rats.